2020
DOI: 10.1021/acs.chemmater.0c03091
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Suprastructures Self-Organized from Oppositely Charged All-Inorganic Nanoparticles

Abstract: The self-organization of colloidal nanoparticles into programmed suprastructures is an important research area in various disciplines of nano, colloid, and polymer sciences. However, despite the recent advances in their fundamental understanding and practical applications, the selforganization of organic-free inorganic nanoparticles remains unexplored. Herein, we present the controlled organization of oppositely charged allinorganic nanoparticles through the electrostatic interaction and the colloidal behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Assuming homogeneous doping, for the 1.5% doped PbTe, the surface density of the dopant exposed to the surface is 7.19 × 10 16 atom m –2 , resulting in a calculated surface charge density of 1.15 × 10 –2 C m –2 , similar to those of other stable colloidal particles, such as polystyrene–latex (PSL), [ 24 ] graphene oxide (GO), reduced GO (rGO), [ 25 ] and nanoparticles. [ 26 ] Several studies have reported similar phenomena for doped particles, for example, Sahu et al. reported that electronic doping of TiO 2 nanoparticles with Cu 2+ caused an increase in the ζ‐potential owing to the charge imbalance between Ti 4+ and Cu 2+ and became stable electrostatically in dispersion.…”
Section: Resultsmentioning
confidence: 85%
“…Assuming homogeneous doping, for the 1.5% doped PbTe, the surface density of the dopant exposed to the surface is 7.19 × 10 16 atom m –2 , resulting in a calculated surface charge density of 1.15 × 10 –2 C m –2 , similar to those of other stable colloidal particles, such as polystyrene–latex (PSL), [ 24 ] graphene oxide (GO), reduced GO (rGO), [ 25 ] and nanoparticles. [ 26 ] Several studies have reported similar phenomena for doped particles, for example, Sahu et al. reported that electronic doping of TiO 2 nanoparticles with Cu 2+ caused an increase in the ζ‐potential owing to the charge imbalance between Ti 4+ and Cu 2+ and became stable electrostatically in dispersion.…”
Section: Resultsmentioning
confidence: 85%
“…MSN-NH 2 exists as a cation in an aqueous solution, but AOS is in the form of an anion in the aqueous solution. Therefore, when MSN-NH 2 and AOS are mixed evenly by mechanical stirring, they self-organize into nanoparticles through electrostatic interaction [49]. The solution of MSN-NH 2 at a low concentration is transparent, with almost no flocculation.…”
Section: Preparation Of Msn-nh 2 -Cur-aos Nanoparticlesmentioning
confidence: 99%
“…LBL assembly results in the formation of multilayer structures whose thicknesses are proportional to the operational number of polycation/polyanion bilayers. 52,138,228 In an example, SbS 4…”
Section: Coating Techniquesmentioning
confidence: 99%
“…Different from the EPD method that relies on external electric field, layer-by-layer (LBL) assembly takes advantage of electrostatic forces by alternating adsorption of positively and negatively charged species from their corresponding solutions. LBL assembly results in the formation of multilayer structures whose thicknesses are proportional to the operational number of polycation/polyanion bilayers. ,, In an example, SbS 4 3– -capped CdSe NCs were assembled into NC multilayer films by sequentially depositing CdSe NCs and Cd 2+ from their solutions (Figure c) . In this case, the capped SbS 4 3– ligands exhibited a strong interaction with Cd 2+ and such intermolecular electrostatic forces acted as the driving forces for the assembly of adjacent NC layers.…”
Section: Applications Of Colloidal Il-capped Ncsmentioning
confidence: 99%